Not that kind of good guy - Ringo, John, 1963- (Baen Publishing Enterprises, 2025)
"It's there for anyone to see: There are dark forces at work on the world, working to destroy civilization. All it takes for evil to triumph is for good men to stand by and do nothing. We need a good guy. For a generation, individuals have arisen with super powers, able to change the course of history, or at least save a few lives. But these people have free will--and not all choose to work for the forces of good. We need someone with an unblotted escutcheon, a Galahad for the 21st Century, someone pure of ethics and morality. What we get is Michael: the product of a broken childhood, raised in the foster system of one of America's most dangerous inner cities, his wisdom comes from drug addicts and whores. Maybe he's not the hero we asked for, but he's the hero we need. And he's about to hit puberty"--